Improving the micro-electrical-discharge drilling performance of carbon fibre-reinforced polymer: role of assisting-electrode and shaped tool. (18th March 2021) - Dutta, Hrishikesh; Debnath, Kishore; Sarma, Deba Kumar
This paper presents the investigation on the fabrication of micro-holes in carbon fibre-reinforced polymer composites using micro-electrical-discharge drilling method coupled with assisting-electrode and rotary tools of copper and brass. Bisphenol-A based epoxy resin LY 556 having medium viscosity and hardener HY 951 were used for the fabrication of composites. The sizes of the fabricated micro-holes were in the range of 600 μm-830 μm. The input factors considered in this experimental endeavour were voltage (120 volts, 150 volts, and 170 volts), pulse duration (10 μs, 20 μs, and 30 μs), and tool speed (200 RPM, 300 RPM, and 400 RPM). The hole profile was studied under an optical microscope and the surface morphology of the micro-hole was analysed by field-emission scanning electron microscope. The voltage was the most significant factor during micro-electrical-discharge drilling of carbon fibre-reinforced polymer. Fibre breakage, matrix burning, matrix melting, and resolidified layer were evident from the field-emission scanning electron microscopic analysis.